2023
DOI: 10.1186/s12884-023-05660-z
|View full text |Cite
|
Sign up to set email alerts
|

The changing epidemiology of syndactyly in Chinese newborns: a nationwide surveillance-based study

Zhi-Yu Chen,
Wen-Yan Li,
Wen-Li Xu
et al.

Abstract: Background Little is known about the epidemiologic features of syndactyly (SD) in Chinese newborns. Methods Using 2007–2019 data from the Chinese Birth Defects Monitoring Network, we conducted a prevalence analysis on overall, isolated and associated syndactyly according to birth year, maternal age, maternal residence, geographic region and infant sex, with special interests in time trends, perinatal outcomes and clinical phenotypes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…However, few studies reported higher prevalences of polydactyly in advanced maternal age. In addition, the occurrence of syndactyly appeared independent of maternal age, consistent with several previous studies [33,48]. However, Hay et al found a positive relation between increasing maternal age and increasing prevalence of syndactyly [49].…”
Section: Discussionsupporting
confidence: 90%
“…However, few studies reported higher prevalences of polydactyly in advanced maternal age. In addition, the occurrence of syndactyly appeared independent of maternal age, consistent with several previous studies [33,48]. However, Hay et al found a positive relation between increasing maternal age and increasing prevalence of syndactyly [49].…”
Section: Discussionsupporting
confidence: 90%